DYNAMICS OF CONTINENTAL RIFT PROPAGATION: THE END-MEMBER MODES - Van Wijk J.W.; Blackman D.K. (My University, 2005)
An important aspect of continental rifting is the progressive variation of deformation style along the rift axis during rift propagation. In regions of rift propagation, specifically transition zones from continental rifting to seafloor spreading, it has been observed that contrasting styles of deformation along the axis of rift propagation are bounded by shear zones. The focus of this numerical modeling study is to look at dynamic processes near the tip of a weak zone in continental lithosphere. More specifically, this study explores how modeled rift behavior depends on the value of rheological parameters of the crust. A three-dimensional finite element model is used to simulate lithosphere deformation in an extensional regime. The chosen approach emphasizes understanding the tectonic forces involved in rift propagation. Dependent on plate strength, two end-member modes are distinguished. The stalled rift phase is characterized by absence of rift propagation for a certain amount of time. Extension beyond the edge of the rift tip is no longer localized but occurs over a very wide zone, which requires a buildup of shear stresses near the rift tip and significant intra-plate deformation. This stage represents a situation in which a rift meets a locked zone. Localized deformation changes to distributed deformation in the locked zone, and the two different deformation styles are balanced by a shear zone oriented perpendicular to the trend. In the alternative rift propagation mode, rift propagation is a continuous process when the initial crust is weak. The extension style does not change significantly along the rift axis and lengthening of the rift zone is not accompanied by a buildup of shear stresses. Model predictions address aspects of previously unexplained rift evolution in the Laptev Sea, and its contrast with the tectonic evolution of, for example, the Gulf of Aden and Woodlark Basin.